Active ageing and older adults’ volunteerism in Asia: a systematic review - Isabela Senti Rijeng; Khadijah Alavi; Siti Fardaniah Abdul Aziz; Jamiah Manap (Penerbit Universiti Kebangsaan Malaysia, 2024)
Volunteerism among older adults has been actively encouraged and adopted as a policy measure among developed countries in view of its benefits and impact on the wellbeing of the elderly. However, there is a paucity of research related to the same effort in Asia even though this region is projected to have the fastest-growing ageing population by the year 2050. Utilising the eight determinants of active ageing as posited by WHO Active Ageing Policy Framework, this paper aimed to identify emerging themes in the existing literature grounded upon older adults’ recent volunteering policies and practices in Asia. A systematic review was performed to explore the literature on older adults’ volunteerism in peer-reviewed journals published in the past decade in two main databases (Scopus and Web of Science). The findings identified from the 19 articles were analysed according to the following themes: (1) culture, (2) gender, (3) behavioural determinants, (4) personal determinants, (5) physical environment, (6) social determinants, (7) economic factors, and (8) health and social services. From the review, behavioural, personal and social environment determinants appeared to be the focal point of active ageing research agenda. A robust and strategic collaboration between policymakers and volunteering stakeholders is key to amplify older adults’ volunteer efforts in line with successful active ageing in Asia.